Building an Interoperability Test System for Electric Vehicle Chargers Based on ISO/IEC 15118 and IEC 61850 Standards - Minho Shin; Hwimin Kim; Hyoseop Kim; Hyuksoo Jang (Applied Sciences, 2016)
The electric vehicle market is rapidly growing due to its environmental friendliness and governmental support. As electric vehicles are powered by electricity, the interoperability between the vehicles and the chargers made by multiple vendors is crucial for the success of the technology. Relevant standards are being published, but the methods for conformance testing need to be developed. In this paper, we present our conformance test system for the electric vehicle charger in accordance with the standards ISO/IEC 15118, IEC 61851 and IEC 61850-90-8. Our test system leverages the TTCN-3 framework for its flexibility and productivity. We evaluate the test system by lab tests with two reference chargers that we built. We also present the test results in two international testival events for the ISO/IEC 15118 interoperability. We confirmed that our test system is robust, efficient and practical.